Mathematical simulation of the motion law of differential mortar pump piston intended for construction mix - Korobko, Bogdan; Zhyhylii, Serhii; Kivshyk, Anton (Academic journal Industrial Machine Building Civil Engineering, 2019)
The paper is dedicated to the creation of a differential mortar pump with electromagnetic action for pumping finishingmaterial, which is not sensitive to electric energy gaps, and which is at the same time convenient, easy to use, reliable andeconomical in operation. The paper presents the mathematical model of the working process dynamics of a differentialmortar pump with electromagnetic action, which will allow to study common patterns of pumping processes in the pump inthe whole, to solve general problems on their calculation and design, to set and solve problems of reliability control,connected with high-frequency pressure oscillations, the problems of structural optimization and optimal design of all itselements. The control system of a pumping unit with vector controlled asynchronous electric drive is proposed on the basis ofthe concept of inverse dynamics problems in combination with the minimization of local functionality of instantaneousenergy magnitudes, which ensures high-quality pressure regulation under the conditions of parametric perturbations activityand has acceptable energy indices.
Keywords: differential mortar pump with electromagnetic action; mathematical modeling; construction mix